Green building with concrete sustainable design and construction - Sabnis, Gajanan M. (CRC Press, 2012)
"Packed with case studies highlighting construction companies that regularly recycle between 70% and 95% of concrete from their waste streams, this book presents practical, up-to-date information about concrete's history in the green building movement, state of the art methodologies, and current best practices. Using the USGBC LEED (Leadership in Energy and Environmental Design) green building assessment standard, the book covers site, energy, water, materials, indoor environmental quality, construction, and demolition waste protocols and provides information on tracking the LEED requirements to assure timely building certification. It also addresses non-LEED issues, such as flood and fire protection benefits"-- Provided by publisher.
Keywords: Concrete construction.; Sustainable construction.; Concrete -- Recycling.; elektronické knihy; electronic books